In Vivo Autofluorescence Imaging of the Human and Macaque Retinal Pigment Epithelial Cell Mosaic - Jessica I. W. Morgan; Alfredo Dubra; Robert Wolfe; William H. Merigan; David R. Williams (2009)
Retinal pigment epithelial (RPE) cells are critical for the health of the retina, especially the photoreceptors. A recent study demonstrated that individual RPE cells could be imaged in macaque in vivo by detecting autofluorescence with an adaptive optics scanning laser ophthalmoscope (AOSLO). The current study extended this method to image RPE cells in fixating humans in vivo and to quantify the RPE mosaic characteristics in the central retina of normal humans and macaques.The retina was imaged simultaneously with two light channels in a fluorescence AOSLO; one channel was used for reflectance imaging of the cones while the other detected RPE autofluorescence. The excitation light was 568 nm, and emission was detected over a 40-nm range centered at 624 nm. Reflectance frames were registered to determine interframe eye motion, the motion was corrected in the simultaneously recorded autofluorescence frames, and the autofluorescence frames were averaged to give the final RPE mosaic image.In vivo imaging demonstrated that with increasing eccentricity, RPE cell density, and mosaic regularity decreased, whereas RPE cell size and spacing increased. Repeat measurements of the same retinal location 42 days apart showed the same RPE cells and distribution.The RPE cell mosaic has been resolved for the first time in alert fixating human subjects in vivo using AOSLO. Mosaic analysis provides a quantitative database for studying normal and diseased RPE in vivo. This technique will allow longitudinal studies to track disease progression and assess treatment efficacy in patients and animal models of retinal disease.